Integration of occupational therapists into family medicine groups: Physicians' perspectives. (July 2020) - Locas, Valérie; Préfontaine, Cassandra; Veillette, Nathalie; Vachon, Brigitte
Introduction: Occupational therapists remain poorly integrated into family medicine groups in Canada. Physicians are key partners because they can advocate for resources and formulate recommendations to improve the quality of services delivered in their clinics. It is important to explore their perception of the occupational therapist's role in family medicine groups and the factors influencing their integration. Method: A descriptive qualitative study was conducted. Six family physicians participated in an individual interview. Results were analysed using thematic analysis. Results: Physicians consider that occupational therapists can meet the needs of diverse primary care clients. Benefits of this integration include improved clients' functional status, early screening for developmental and age-related problems, and timely access to required care. The main barriers to integration are lack of funding, space and knowledge of the occupational therapist's role. The strategies identified to facilitate integration are promoting and clarifying the role of occupational therapists in family medicine groups and developing effective integration models. Conclusion: According to physicians, the inclusion of occupational therapists in family medicine groups could help primary care teams address many of their clients' needs and improve the overall quality of primary care services. Targeted strategies are needed to promote the integration of occupational therapists into this practice context.